(3cJGH aj GdSjQI hGdZRhGJs
(3ChdgG (B:s
(3Chdg eHJhQ, hjHOC eGajg HPcQ cJH QShd Gddg Udi Gddg Ydjg hSde Edi Gdedhc, hChdg(B: (3bGdhG(B: (3hdeG hLg QShd Gddg Udi Gddg Ydjg hSde Edi edhc GdCQV jOYhge Edi GdESdGe s
(3BNQgG (B:s
(3hBNQg eHJhQ CjVkG, hjfJgj GdehLhO efg(B: (3aCbGe eYGhjI Ydi GdTGe HbjI NdGaI YeQ, Ke CbQg YdjgG YKeGf EKfJi YTQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B341 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs